2021
DOI: 10.3390/cancers13071604
|View full text |Cite
|
Sign up to set email alerts
|

Long, Noncoding RNA Dysregulation in Glioblastoma

Abstract: Transcription occurs across more than 70% of the human genome and more than half of currently annotated genes produce functional noncoding RNAs. Of these transcripts, the majority—long, noncoding RNAs (lncRNAs)—are greater than 200 nucleotides in length and are necessary for various roles in the cell. It is increasingly appreciated that these lncRNAs are relevant in both health and disease states, with the brain expressing the largest number of lncRNAs compared to other organs. Glioblastoma (GBM) is an aggress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 134 publications
0
18
0
Order By: Relevance
“…Given the sizable studies of the role for lncRNAs cellular processes [ 34 , 36 ] made them important to be considered in the context of GBM heterogeneity and treatment resistance. In the current study the median follow-up for GBM patients was 10 months and the estimated median PFS was 11 months and median OS was 13 months which concurrent with the median follow up period of previous studies on GBM [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the sizable studies of the role for lncRNAs cellular processes [ 34 , 36 ] made them important to be considered in the context of GBM heterogeneity and treatment resistance. In the current study the median follow-up for GBM patients was 10 months and the estimated median PFS was 11 months and median OS was 13 months which concurrent with the median follow up period of previous studies on GBM [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the sizable studies of the role for lncRNAs cellular processes 31,29 made them important to be considered in the context of GBM heterogeneity and treatment resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The functional versatility of lncRNAs is related to their ability to conform to various structures and molecular interactions with DNA, RNA and proteins [ 64 ]. The relationship of lncRNAs to the development of glioblastoma has already been described in a number of reviews [ 65 , 66 , 67 ] and studied in meta-analyses [ 68 , 69 ], which have already identified potential targets for developing diagnosis, prognosis assessment, and combination therapy. LncRNAs can indirectly affect the post-translational modifications of RNA, and hence can affect processes of oncogenesis such as apoptosis.…”
Section: Non-coding Rna and Apoptosismentioning
confidence: 99%